2020
DOI: 10.1021/acs.langmuir.0c01689
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Wettability Influences Internal Jet Formation and Mixing during Droplet Coalescence

Abstract: The internal dynamics during the axisymmetric coalescence of an initially static free droplet and a sessile droplet of the same fluid are studied using both laboratory experiments and numerical simulations. A high-speed camera captured internal flows from the side, visualized by adding a dye to the free droplet. The numerical simulations employ the volume of fluid method, with the Kistler dynamic contact angle model to capture substrate wettability, quantitatively validated against the image-processed experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…To represent the influence of dynamic apparent contact angle θ d , we compiled the Kistler model in the interFoam solver. The algorithm is used for every time step and can be written as where θ e is the equilibrium contact angle and f H –1 is the inverse function of the Hoffman empirical function, which can be obtained by and Ca is the capillary number defined as where v cl is the contact line velocity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To represent the influence of dynamic apparent contact angle θ d , we compiled the Kistler model in the interFoam solver. The algorithm is used for every time step and can be written as where θ e is the equilibrium contact angle and f H –1 is the inverse function of the Hoffman empirical function, which can be obtained by and Ca is the capillary number defined as where v cl is the contact line velocity.…”
Section: Methodsmentioning
confidence: 99%
“…To represent the influence of dynamic apparent contact angle θ d , we compiled the Kistler model 56 in the interFoam solver. The algorithm is used for every time step and can be written as…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a key limitation in VOF approaches -and Navier-Stokes based approaches in general -is that the dynamic contact angle θ d usually has to be prescribed as an input. For relatively well-behaved systems, empirical relations between θ d and the contact-line velocity U can be used (Yokoi et al 2009;Sykes et al 2020b). However, for a complex 3-D geometry evolving in time, as considered here, this is not straightforward.…”
Section: Computational Methodologymentioning
confidence: 99%
“…For 'open-surface' droplet-based microfluidics, a wettability gradient surface [24][25][26] is a common way to promote the droplet mixing. Recently, Sykes et al [27] found that the mixing could be improved by the formation of an internal jet. The influence of substrate wettability, the volume ratio and droplet viscosity on the formation of the jet were studied by means of experiments and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%